THE INFLUENCE OF SEASONALITY ON LIVE-DEAD FIDELITY OF CAENOGASTROPODA FROM THE NORTHERN COAST OF SO PAULO STATE, BRAZIL - Limeira Junior, Silvio Cesar Marqui; Martins, Henrique Bazzo; Perroca, Júlia Fernandes; Rodrigues, Sabrina Coelho; Ghilardi, Renato Pirani (Society for Sedimentary Geology, 2024)
Abstract Environmental seasonality produces variations in the distribution and structure of biodiversity throughout the year. Understanding how ecological fidelity is affected by these variations allows taphonomists to assess not only the degree of fidelity, but also to identify which seasonal assemblage the fossil record reflects. The present study aims to evaluate the fidelity of gastropod mollusks from a tropical soft substrate environment (Ubatuba Bay, Brazil) collected over a 12-month interval. Samples were collected at four sites within a bathymetric interval of 5–15 m. After the taxonomic assessment, statistical analysis of the live-dead assemblages was conducted. For biodiversity, the total number of shells per sampling site, relative abundance, and species richness, as well as the Shannon index were used. Fidelity was based on the relative percentages of species between the living and dead assemblages and similarity between them was measured by the Sørensen index. Our results show that during stable rainfall/fluvial conditions, the number of dead individuals was low, and fidelity was low while during intense turbidity and subsequent death of gastropods, the abundance of dead individuals increased, and fidelity became high. Only at collection site P4, during intense rainfall/fluvial conditions, the diversity and similarity indices showed significant values. The clockwise circulation of water masses within the bay and the upwelling currents in summer, coupled with the physical-geographical barrier at P4, explain the accumulation of shells at the site, as well as its seasonal behavior. Thus, seasonality exhibited a direct impact on the live-dead fidelity of soft-substrate Caenogastropoda from Ubatuba Bay, Brazil.